2022
DOI: 10.1186/s12888-022-04189-3
|View full text |Cite
|
Sign up to set email alerts
|

Validation of brief screening instruments for internalizing and externalizing disorders in Mozambican adolescents

Abstract: Background Mental disorders are the leading cause of disability for youth worldwide. However, there is a dearth of validated, brief instruments to assess mental health in low- and middle-income countries (LMIC). We aimed to facilitate identification of mental disorders in LMIC contexts by adapting and validating measures of internalizing and externalizing disorders for adolescents in Mozambique, an LMIC in southeastern Africa. Methods We selected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 64 publications
3
11
0
Order By: Relevance
“…The Spearman correlation coefficient of the scale was 0.70, which suggested good test–retest reliability for the scale, indicating the stability of the PHQ-A. These findings align with prior studies [ 27 – 29 ]. The satisfactory internal reliability and fair test-retest reliability of the PHQ-A confirmed its acceptable reliability among Chinese adolescents with MDD.…”
Section: Discussionsupporting
confidence: 89%
“…The Spearman correlation coefficient of the scale was 0.70, which suggested good test–retest reliability for the scale, indicating the stability of the PHQ-A. These findings align with prior studies [ 27 – 29 ]. The satisfactory internal reliability and fair test-retest reliability of the PHQ-A confirmed its acceptable reliability among Chinese adolescents with MDD.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, although race is a factor influencing the level of stress and anxiety, no study has mentioned to our knowledge that this factor can impact the perception of the items or the scale structure. Additionally, after a review of the international literature aiming to assess the structural validity of GAD-7 in different populations, an absence of the racial factor in data collection is noticeable [ 13 , 15 , 18 , 19 , 20 , 21 , 22 ], affirming the argument that it would not have an impact on the perception of items or on the structure of the scale. However, this study demonstrates relevant information that needs to be carefully taken into consideration in future screening studies of the general population of French adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…However, the measurement properties have not been demonstrated in the French youth population. Recent studies have shown increasing interest in validating GAD-7 and other self-assessment questionnaires in adolescent and pediatric populations [ 13 , 15 , 18 , 19 , 20 , 21 , 22 ] in different languages, as concern grows for the mental well-being of youngsters and as early detection is considered an important factor in the successful treatment of mental disorders. Adolescents could potentially have a different understanding of certain items when compared to their adult counterparts, either due to a less developed vocabulary or due to a different generational perception of certain terms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A score of 5–9, 10–14, 15–19, and 20–27 represents the cut-off points for mild, moderate, moderately severe, and severe depression, respectively. PHQ-9 has been used and validated for use in adolescents from Africa [ 2 , 20 , 43 ]. The tool has been validated in the Swahili language [ 24 ].…”
Section: Methodsmentioning
confidence: 99%